An overview of the key routes to the best selling 5-membered ring heterocyclic pharmaceuticals - Baumann, Marcus; Baxendale, Ian R.; Ley, Steven V.; Nikbin, Nikzad (Beilstein Journal of Organic Chemistry, 2011)
This review presents a comprehensive overview on selected synthetic routes towards commercial drug compounds as published in both journal and patent literature. Owing to the vast number of potential structures, we have concentrated only on those drugs containing five-membered heterocycles and focused principally on the assembly of the heterocyclic core. In order to target the most representative chemical entities the examples discussed have been selected from the top 200 best selling drugs of recent years.
Keywords: five-membered rings; heterocycles; medicinal chemistry; pharmaceuticals; synthesis

(untitled) - McGrath, N. A.; Brichacek, M.; Njardarson, J. T. (J. Chem. Educ., 2010)

(untitled) - Roth, B. D.; Blankley, C. J.; Chucholowski, A. W.; Ferguson, E.; Hoefle, M. L.; Ortwine, D. F.; Newton, R. S.; Sekerke, C. S.; Sliskovic, D. R.; Wilson, M. (J. Med. Chem., 1991)

U.S. Patent - Roth, B. D. (Trans-6-[2-(3- or 4-carboxamido-substituted pyrrol-1-yl)alkyl]-4-hydroxypyran-2-one Inhibitors of Cholesterol Synthesis, 1987)

(untitled) - Sagyam, R. R.; Padi, P. R.; Ghanta, M. R.; Vurimidi, H. (J. Heterocycl. Chem., 2007)

WO Patent - Butler, D. E.; Deering, C. F.; Millar, A.; Nanninga, T. N.; Roth, B. D. (Improved Process for Trans-6-[2-(substituted-pyrrole-1-yl)alkyl]pyran-2-one Inhibitors of Cholesterol Synthesis, 1989)

U.S. Patent - Butler, D. E.; Le, T. V.; Millar, A.; Nanninga, T. N. (Process for the Synthesis of (5R)-1,1-Dimethylethyl-6-cyano-5-hydroxy-3-oxohexanoate, 1992)

(untitled) - Gajiwala, K. S.; Wu, J. C.; Christensen, J.; Deshmukh, G. D.; Diehl, W.; DiNitto, J. P.; English, J. M.; Greig, M. J.; He, Y.-A.; Jacques, S. L.; Lunney, E. A.; McTigue, M.; et al. (Proc. Natl. Acad. Sci. U. S. A., 2009)

Process Chemistry in the Pharmaceutical Industry - Vaidyanathan, R. (The SUTENT® Story, 2008)

(untitled) - Pete, B.; Bitter, I.; Szántay, C., Jr; Schön, I.; Töke, L. (Heterocycles, 1998)

U.S. Patent - Oxford, A. W. (Indole Derivative, 1991)

(untitled) - Japp, F. R.; Klingemann, F. (Chem. Ber., 1887)

(untitled) - Pete, B.; Bitter, I.; Harsányi, K.; Töke, L. (Heterocycles, 2000)

(untitled) - Kim, D.-W.; Ko, Y. K.; Kim, S. H. (Synthesis, 1992)

U.S. Patent - Albinson, F. D.; MacKinnon, J. W. M.; Crookes, D. L. (Preparation of Indole Derivatives, 1992)

(untitled) - Zhou, G.; Ting, P.; Aslanian, R.; Piwinski, J. J. (Org. Lett., 2008)

WO Patent - Blatcher, P.; Carter, M.; Hornby, R.; Owen, M. (Process for the Preparation of N-Methyl-3-(1-methyl-4-piperidinyl)-4-indole-5-ethanesulphonamide, 1995)

(untitled) - Buckingham, J.; Glen, R. C.; Hill, A. P.; Hyde, R. M.; Martin, G. R.; Robertson, A. D.; Salmon, J. A.; Woollard, P. M. (J. Med. Chem., 1995)

WO Patent - Voslar, M.; Zatopkova, M.; Ridvan, L.; Pekarek, T. A. (Method for the Preparation of Zolmitriptan, 2008)

U.S. Patent - Baker, R.; Matassa, V. G.; Street, L. J. (Triazole Containing Indole Derivatives, 1994)

(untitled) - Street, L. J.; Baker, R.; Davey, W. B.; Guiblin, A. R.; Jelley, R. A.; Reeve, A. J.; Routledge, H.; Sternfeld, F.; Watt, A. P. (J. Med. Chem., 1995)

WO Patent - Koilpillai, J. P.; Subramanian, M.; Mallela, U.; Boddu, V. B.; Dandala, R.; Meenakshisunderam, S. (An Improved Process for the Preparation of Rizatriptan, 2008)

(untitled) - Larock, R. C.; Yum, E. K.; Refvik, M. D. (J. Org. Chem., 1998)

(untitled) - Chen, C.-y.; Lieberman, D. R.; Larsen, R. D.; Reamer, R. A.; Verhoeven, T. R.; Reider, P. J.; Cottrell, I. F.; Houghton, P. G. (Tetrahedron Lett., 1994)

WO Patent - Muddasani, P. R.; Hanumara, S. R.; Kagitha, R.; Nannapaneni, V. C. (Improved Process for the Preparation of Rizatriptan Benzoate, 2006)

WO Patent - Chen, C. Y.; Larsen, R. D.; Verhoeven, T. R. (Palladium Catalyzed Ring Closure of Triazolyl Tryptamine, 1995)

U.S. Patent - Macor, J. E.; Wythes, M. J. (Indole Derivatives, 1996)

Eur. Patent - Perkins, J. F. (Process for the Preparation of 3-Acylindoles, 2001)

WO Patent - Ashcroft, C. P. (Modified Fischer Indole Synthesis for Eletriptan, 2005)

(untitled) - Bischler, A. (Chem. Ber., 1892)

(untitled) - Sridharan, V.; Perumal, S.; Avendaño, C.; Menéndez, J. C. (Synlett, 2006)

(untitled) - Repič, O.; Prasad, K.; Lee, G. T. (Org. Process Res. Dev., 2001)

(untitled) - Walkup, R. E.; Linder, J. (Tetrahedron Lett., 1985)

U.S. Patent - Godfrey, N.; Coates, I. H.; Bell, J. A.; Humber, D. C.; Ewan, G. B. (Process for Preparing N-Heterocyclic Compounds, 1990)

(untitled) - Iida, H.; Yuasa, Y.; Kibayashi, C. (J. Org. Chem., 1980)

U.S. Patent - Oxford, A. W.; Eldred, C. D.; Coates, I. H.; Bell, J. A.; Humber, D. C.; Ewan, G. B. (Process for Preparing Tetrahydrocarbazolones, 1988)

U.S. Patent - Daugan, A. C.-M. (Tetracyclic Derivatives; Process of Preparation and Use, 1999)

U.S. Patent - Daugan, A. C.-M. (Tetracyclic Derivatives, Process of Preparation and Use, 2000)

(untitled) - Shi, X.-X.; Liu, S.-L.; Xu, W.; Xu, Y.-L. (Tetrahedron: Asymmetry, 2008)

(untitled) - Yue, T.-L.; Cheng, H.-Y.; Lysko, P. G.; McKenna, P. J.; Feuerstein, R.; Gu, J.-L.; Lysko, K. A.; Davis, L. L.; Feuerstein, G. (J. Pharmacol. Exp. Ther., 1992)

U.S. Patent - Lauer, K.; Kiegel, E. (Process for the Preparation of 4-Hydroxycarbazole, 1981)

(untitled) - Huang, S.; Yu, H.; Sun, X.; Gao, W. (Zhongguo Yaowu Huaxue Zazhi, 2000)

U.S.Patent - Demerson, C. A.; Humber, L. G.; Dobson, T.; Jirkovsky, I. L. (Certain pyrano[3,4-B]indoles and thiopyrano[3,4-B]indoles, 1976)

U.S. Patent - Demerson, C. A.; Humber, L. G. (Process for Preparing 1,8-Diethyl-1,3,4,9-tetrahydropyrano(3,4-b)-indole-1-acetic acid, Etodolac, 1986)

U.S. Patent - Vincenzo, G.; Franco, P. (3-(2-Trialkylsilyloxy)ethyl-7-ethyl-1H-indoles and Method for their Preparation, 1997)

(untitled) - Woods, M.; Dyer, U. C.; Andrews, J. F.; Morfitt, C. N.; Valentine, R.; Sanderson, J. (Org. Process Res. Dev., 2000)

(untitled) - De Gasparo, M.; Catt, K. J.; Inagami, T.; Wright, J. W.; Unger, T. (Pharmacol. Rev., 2000)

(untitled) - Bühlmayer, P.; Furet, P.; Criscione, L.; de Gasparo, M.; Whitebread, S.; Schmidlin, T.; Lattmann, R.; Wood, J. (Bioorg. Med. Chem. Lett., 1994)

(untitled) - Shi, Y.-J.; Frey, L. F.; Tschaen, D. M.; Verhoeven, T. R. (Synth. Commun., 1993)

(untitled) - Griffiths, G. J.; Hauck, M. B.; Imwinkelried, R.; Kohr, J.; Roten, C. A.; Stucky, G. C.; Gosteli, J. (J. Org. Chem., 1999)

(untitled) - Zhong, Y.-L.; Lee, J.; Reamer, R. A.; Askin, D. (Org. Lett., 2004)

U.S. Patent - Yanagisawa, H.; Fujimoto, K.; Amemiya, Y.; Shimoji, Y.; Kanazaki, T.; Koike, H.; Sada, T. (Angiotensin II Antagonist 1-Biphenylmethylimidazole Compounds and their Therapeutic Use, 1997)

(untitled) - Yanagisawa, H.; Amemiya, Y.; Kanazaki, T.; Shimoji, Y.; Fujimoto, K.; Kitahara, Y.; Sada, T.; Mizuno, M.; Ikeda, M.; Miyamoto, S.; Furukawa, Y.; Koike, H. (J. Med. Chem., 1996)

U.S. Patent - Tyers, M. B.; Coates, I. H.; Humber, D. C.; Ewan, G. B.; Bell, J. A. (Method for Treating Nausea and Vomiting, 1988)

(untitled) - Gitis, K. M.; Raevskaya, N. I.; Isagulyants, G. V. (Russ. Chem. Bull., 1992)

(untitled) - Elz, S.; Heil, W. L. (Bioorg. Med. Chem. Lett., 1995)

(untitled) - Uchida, M.; Morita, S.; Chihiro, M.; Kanbe, T.; Yamasaki, K.; Yabuuchi, Y.; Nakagawa, K. (Chem. Pharm. Bull., 1989)

U.S. Patent - Lindberg, P. L.; Von Unge, S. (Compositions, 1998)

WO Patent - Cotton, H.; Kronström, A.; Mattson, A.; Möller, E. (Novel Form of S-Omeprazole, 1998)

Eur. Patent - Rainer, G.; Riedel, R.; Senn-Biffinger, J.; Klemm, K.; Schaefer, H.; Figaia, V. (Fluoroalkoxysubstituted Pyridylmethylthio-(or Sulfinyl)-benzimidazoles, 1993)

Eur. Patent - Hashimoto, H.; Hanaoka, T.; Kato, M. (Production Method of Aminobenzene Compound, 1998)

(untitled) - Snieckus, V. (Chem. Rev., 1990)

(untitled) - Porcs-Makkay, M.; Mezei, T.; Simig, G. (Org. Process Res. Dev., 2007)

(untitled) - Ries, U. J.; Mihm, G.; Narr, B.; Hasselbach, K. M.; Wittneben, H.; Entzeroth, M.; van Meel, J. C. A.; Wienen, W.; Hauel, N. H. (J. Med. Chem., 1993)

(untitled) - Reddy, K. S.; Srinivasan, N.; Reddy, C. R.; Kolla, N.; Anjaneyulu, Y.; Venkatraman, S.; Bhattacharya, A.; Mathad, V. T. (Org. Process Res. Dev., 2007)

U.S. Patent - Rossey, G.; Long, D. (Process for the Preparation of Imidazopyridines, 1988)

(untitled) - George, P.; Rossey, G.; Depoortere, H.; Mompon, B.; Allen, J.; Wick, A. (Farmaco, 1991)

(untitled) - Chernyak, N.; Gevorgyan, V. (Angew. Chem., Int. Ed., 2010)

(untitled) - Zhu, J.; Song, X.; Lin, H.-P.; Young, D. C.; Yan, S.; Marquez, V. E.; Chen, C.-S. (J. Natl. Cancer Inst., 2002)

(untitled) - Rimon, G.; Sidhu, R. S.; Lauver, D. A.; Lee, J. Y.; Sharma, N. P.; Yuan, C.; Frieler, R. A.; Trievel, R. C.; Lucchesi, B. R.; Smith, W. L. (Proc. Natl. Acad. Sci. U. S. A., 2010)

(untitled) - Penning, T. D.; Talley, J. J.; Bertenshaw, S. R.; Carter, J. S.; Collins, P. W.; Docter, S.; Graneto, M. J.; Lee, L. F.; Malecha, J. W.; Miyashiro, J. M.; Rogers, R. S.; Rogier, D. J.; et al. (J. Med. Chem., 1997)

WO Patent - Talley, J. J.; Penning, T. D.; Collins, P. W.; Rogier, D. J., Jr; Malecha, J. W.; Miyashiro, J. M.; Bertenshaw, S. R.; Khanna, I. K.; Granets, M. J.; Rogers, R. S.; Carters, J. S.; Docter, S. H. (Substituted Pyrazolylbenzenesulfonamides for the Treatment of Inflammation, 1995)

WO Patent - Reddy, M. V. R.; Bell, S. C. (Processes for the Preparation of 1,5-diaryl-3-substituted Pyrazoles, 2003)

(untitled) - Oh, L. M. (Tetrahedron Lett., 2006)

WO Patent - Pandite, A. N.; Whitehead, B. F.; Ho, P. T. C.; Suttle, A. B. (Cancer Treatment Method, 2007)

(untitled) - Harris, P. A.; Boloor, A.; Cheung, M.; Kumar, R.; Crosby, R. M.; Davis-Ward, R. G.; Epperly, A. H.; Hinkle, K. W.; Hunter, R. N., III; Johnson, J. H.; Knick, V. B.; Laudeman, C. P.; et al. (J. Med. Chem., 2008)

WO Patent - Ray, P. C.; Bandari, M.; Qadeeruddin, M.; Manjaneyulu, G. S. (Process for the Large Scale Production of Rizatriptan Benzoate, 2007)

WO Patent - Solanki, K. S.; Pal, G.; Haider, H.; Singh, M.; Kothari, J. S.; Agarwal, V. K. (A Process for the Preparation of Pure Anastrozole, 2007)

WO Patent - Gaitonde, A.; Vaidaya, C.; Pawar, S. R. (Process for the Preparation of Anastrozole, 2006)

(untitled) - Grundmann, C.; Ratz, R. (J. Org. Chem., 1956)

WO Patent - Martin, P.; Berens, U.; Boudier, A.; Dosenbach, O. (Synthesis Methods and Intermediates for the Manufacture of Rizatriptan, 2005)

(untitled) - Kim, D.; Wang, L.; Beconi, M.; Eiermann, G. J.; Fisher, M. H.; He, H.; Hickey, G. J.; Kowalchick, J. E.; Leiting, B.; Lyons, K.; Marsilio, F.; McCann, M. E.; et al. (J. Med. Chem., 2005)

(untitled) - Hansen, K. B.; Balsells, J.; Dreher, S.; Hsiao, Y.; Kubryk, M.; Palucki, M.; Rivera, N.; Steinhuebel, D.; Armstrong, J. D., III; Askin, D.; Grabowski, E. J. J. (Org. Process Res. Dev., 2005)

(untitled) - Balsells, J.; DiMichele, L.; Liu, J.; Kubryk, M.; Hansen, K.; Armstrong, J. D., III (Org. Lett., 2005)

(untitled) - Haycock-Lewandowski, S. J.; Wilder, A.; Åhman, J. (Org. Process Res. Dev., 2008)

(untitled) - Hester, J. P., Jr; Rudzik, A. D.; Kamdar, B. V. (J. Med. Chem., 1971)

(untitled) - Sternbach, L. H.; Fryer, R. I.; Metlesics, W.; Reeder, E.; Sach, G.; Saucy, G.; Stempel, A. (J. Org. Chem., 1962)

(untitled) - Fustero, S.; González, J.; del Pozo, C. (Molecules, 2006)

(untitled) - Heeres, J.; Backx, L. J. J.; Van Cutsem, J. (J. Med. Chem., 1984)

WO Patent - Portmann, R. (Process for preparing 1-substituted 4-cyano-1,2,3-triazoles, 1998)

US Patent - Portmann, R.; Hofmeier, C.; Burkhard, A.; Scherrer, W.; Szelagiewicz, M. (Crystal modification of 1-(2,6-difluorobenzyl)-1H-1,2,3-triazole-4-carboxamide and its use as antiepileptic, 2004)

(untitled) - Hudd, W. H.; Stevens, E. P. (Tetrahedron Lett., 2010)

WO Patent - Wang, Y.; Li, Y.; Li, Y.; Zheng, G.; Li, Y. (Method for the Production of Losartan, 2006)

U.S. Patent - Mendelovici, M.; Finkelstein, N.; Pilarski, G. (Process for Preparing Cilostazol, 2003)

U.S. Patent - Nishi, T.; Nakagawa, K. (Tetrazolylalkoxycarbostyryl Derivatives and Pharmaceutical Compositions Containing them, 1981)

(untitled) - Guay, D. R. P. (Clin. Ther., 2002)

(untitled) - Mooney, M. T.; Deguchi, S.; Tada, T.; Fujioka, M.; Okamoto, Y.; Yasuda, T. (Chem. Pharm. Bull., 1995)

(untitled) - González, M.; Rodriguez, Z.; Tolón, B.; Rodriguez, J. C.; Veléz, H.; Valdez, B.; Lopéz, M. A.; Fini, A. (Farmaco, 2003)

(untitled) - Kempf, D. J.; Marsh, K. C.; Denissen, J. F.; McDonald, E.; Vasavanonda, S.; Flentge, C. A.; Green, B. E.; Fino, L.; Park, C. H.; Kong, X. P. (Proc. Natl. Acad. Sci. U. S. A., 1995)

(untitled) - Kerdesky, F. A. J.; Seif, L. S. (Synth. Commun., 1995)

Eur. Patent - Schneider, C.; Griss, G.; Hurnaus, R.; Kobinger, W.; Pichler, L.; Bauer, R.; Mierau, J.; Hinzen, D.; Schingnitz, G. (Tetrahydrobenzothiazoles, their Production and Use as Intermediates and Pharmaceuticals, 1986)

WO Patent - Martin Juarez, J.; Silva Guisasola, L. O. (Method for the Resolution of 2-Amino-6-propylamino-4,5,6,7-tetrahydrobenzothiazole and Intermediate Compounds, 2006)

(untitled) - Miodragović, D. U.; Bogdanović, G. A.; Miodragović, Z. M.; Radulović, M. Đ.; Novaković, S. B.; Kaluđerović, G. N.; Kozłowski, H. (J. Inorg. Biochem., 2006)

(untitled) - Sprague, J. M.; Land, A. H.; Ziegler, C. (J. Am. Chem. Soc., 1946)

U.S. Patent - Hirata, Y.; Yanagisawa, I.; Ishii, Y.; Tsukamoto, S.; Ito, N.; Isamura, Y.; Takeda, M. (Guanidinothiazole Compounds, Process for Preparation and Gastric Inhibiting Compositions Containing them, 1981)

(untitled) - Hasegawa, M. (Heterocycles, 1998)

(untitled) - Yevich, J. P.; New, J. S.; Smith, D. W.; Lobeck, W. G.; Catt, J. D.; Minielli, J. L.; Eison, M. S.; Taylor, D. P.; Riblet, L. A.; Temple, D. L., Jr (J. Med. Chem., 1986)

(untitled) - Nadkarni, D. V.; Hallissey, J. F. (Org. Process Res. Dev., 2008)

(untitled) - Walinsky, S. W.; Fox, D. E.; Lambert, J. F.; Sinay, T. G. (Org. Process Res. Dev., 1999)

Eur. Patent - Huguet Clotet, J.; Puig Torres, S. (Process for the Preparation of Ziprasidone, 2008)

Ger. Patent - Price, B. J.; Clitherow, J. W.; Bradshaw, J. W. (Aminoalkylfuranderivate, Verfahren zu ihrer Herstellung und diese Verbindungen erhaltende Arzneimittel, 1983)

(untitled) - Vlaovic, D.; Milic, B. L.; Mackenzie, K. (J. Chem. Res., Synop., 1989)

U.S. Patent - Gever, G.; O’Keefe, C. J. (Process for the Preparation of Azomethines of 5-Nitro-2-formylfurane with Hydrazine Compounds, 1960)

(untitled) - Witczak, M.; Kwiecień, H. (Synth. Commun., 2005)

Chin. Patent - Wang, Z. J. (Synthetic Process for 2-Butyl-3-(hydroxy-3,5-diiodobenzoyl)-benzofuran, 2006)

(untitled) - Ha, H. R.; Stieger, B.; Grassi, G.; Altorfer, H. R.; Follath, F. (Eur. J. Clin. Pharmacol., 2000)

(untitled) - Vogel, V. G.; Costantino, J. P.; Wickerham, D. L.; Cronin, W. M.; Cecchini, R. S.; Atkins, J. N.; Bevers, T. B.; Fehrenbacher, L.; Pajon, E. R., Jr; Wade, J. L., III; Robidoux, A.; Margolese, R. G.; et al. (JAMA, J. Am. Med. Assoc., 2006)

(untitled) - Jones, C. D.; Jevnikar, M. G.; Pike, A. J.; Peters, M. K.; Black, L. J.; Thompson, A. R.; Falcone, J. F.; Clemens, J. A. (J. Med. Chem., 1984)

WO Patent - Aikins, J. A.; Miller, R. S. (Vinyl Sulfoxides and a Process for their Synthesis, 1996)

U.S. Patent - Chakrabarti, J. K.; Hotten, T. M.; Tupper, D. E. (2-Methylthienobenzodiazepine, 1997)

U.S. Patent - Chakrabarti, J. K.; Hotten, T. M.; Tupper, D. E. (2-Methylthienobenzodiazepine, 1993)

U.S. Patent - Berglund, R. A. (Intermediate Useful for the Asymmetric Synthesis of Duloxetine, 1996)

U.S. Patent - Eng, W.-S.; Burns, D. H.; Ponticello, G. S.; Selwick, H. G. (Short Synthesis of 5,6-Dihydro-(S)-4-(ethylamino)-(S)-6-[C3H3]-4H-thieno[2,3-b]thiopyran-2-sulfonamide-7,7-dioxide and Related Non-Radioactive Compounds, 1995)

(untitled) - Blacklock, T. J.; Sohar, P.; Butcher, J. W.; Lamanec, T.; Grabowski, E. J. J. (J. Org. Chem., 1993)

(untitled) - Wang, L.; Shen, J.; Tang, Y.; Chen, Y.; Wang, W.; Cai, Z.; Du, Z. (Org. Process Res. Dev., 2007)

Eur. Patent - Lodewijk, E.; Khatri, H. N. (2-(2-Nitrovinyl)thiophene Reduction and Synthesis of Thieno[3,2-c]pyridine Derivatives, 1989)

(untitled) - Kikuchi, C.; Hiranuma, T.; Koyama, M. (Bioorg. Med. Chem. Lett., 2002)

(untitled) - Hanson, M. A.; Cherezov, V.; Griffith, M. T.; Roth, C. B.; Jaakola, V.-P.; Chien, E. Y. T.; Velasquez, J.; Kuhn, P.; Stevens, R. C. (Structure, 2008)

(untitled) - Tosi, G.; Zironi, F.; Caselli, E.; Forni, A.; Prati, F. (Synthesis, 2004)

U.S. Patent - Vest, R. D. (3,4-Dichloro-1,2,5-thiadiazole and its Preparation, 1963)

(untitled) - Xu, J.; Shen, Y.; Xiang, L.; Deng, Y. (Zhongguo Yiyao Gongye Zazhi, 2005)

(untitled) - Lima, L. M.; Barreira, E. J. (Curr. Med. Chem., 2005)

WO Patent - Ramakrishnam, A.; Gobind, K.; Neeraj, K.; Dnyaneshwar, S. (An Improved Process for Preparation of Leflunomides, 2007)

Jap. Patent - Ikuno, K.; Yoshida, S. (Method for Producing 5-Methylisoxazole, 2007)

(untitled) - Reiter, L. A. (J. Org. Chem., 1987)

U.S. Patent - Kennis, L. E. J.; Vanderberk, J. (3-Piperidinyl-substituted 1,2-Benzisoxazoles and 1,2-Benzisothiazoles, 1989)

(untitled) - Carey, J. S.; Laffan, D.; Thomson, C.; Williams, M. T. (Org. Biomol. Chem., 2006)

(untitled) - Dugger, R. W.; Ragan, J. A.; Brown Ripin, D. H. (Org. Process Res. Dev., 2005)

Chirality in Drug Research: From Synthesis to Pharmacology - Francotte, E.; Lindner, W. (Wiley-VCH Verlag GmbH & Co. KgaA, 2006)

Catalytic Asymmetric Synthesis - Ojima, I. (Wiley & Sons, Inc., 2010)

(untitled) - Baxendale, I. R.; Hayward, J. J.; Ley, S. V.; Tranmer, G. K. (ChemMedChem, 2007)